Comparison of perinatal outcomes between long‐term and short‐term use of tocolytic agent: a historical cohort study in a single perinatal hospital. Issue 12 (19th September 2016) - Nakamura, Masamitsu; Hasegawa, Junichi; Arakaki, Tatsuya; Hamada, Shoko; Takita, Hiroko; Oba, Tomohiro; Koide, Keiko; Matsuoka, Ryu; Sekizawa, Akihiko
Abstract: Aim: The aim of this study was to evaluate the effect of long‐term use of tocolytic agents to prevent preterm delivery and improve perinatal outcome. Methods: A historical cohort study was performed in a single perinatal center. The maternal characteristics, frequency of preterm labor and prescribed dose of tocolytic agents were compared before and after changing the management protocol for threatened premature delivery. Results: A total of 1548 deliveries were carried out before changing the protocol for the use of tocolytic agents for threatened premature delivery and 1444 deliveries afterwards. There was no significant difference in the maternal characteristics before and after the revision except for maternal age. The total number of ritodrine hydrochloride ampules used was reduced from 4654 to 514, and the total vials of magnesium sulfate used were reduced from 1574 to 193, but perinatal outcomes, such as rate of preterm birth, neonatal weight, and rate of NICU hospitalization were not different between the groups. Conclusion: There was no significant change in the frequency of preterm delivery before and after changing of the protocol for threatened premature delivery. Because a decrease in the given dose of tocolytic agents did not affect the timing of delivery and neonatal outcomes, long‐term tocolysis in patients with threatened premature delivery should be restricted to prevent maternal and fetal adverse side‐effects.